The Effect of Macro Economic Variables upon Bali’s Economic Growth Moderated by Inflation in COVID-19 Pandemic - Desak Ayu Sriary Bhegawati Desak Ayu (Global Academia Publisher, 2020)
Economic growth comes with the increasing growth of consumption and investment. This element is beneficial since it provides inputs for national income. Controlled inflation can maintain economic stability and increase economic growth. However, due to Covid-19, Bali's economic growth has gone into decline. This study aims to determine the effect of consumption and investment on economic growth in Bali moderated by inflation. The data were analyzed by moderated regression analysis, in which consumption and investment demonstrably have a positive and significant effect on economic growth. In addition, inflation moderates the effect of consumption on economic growth, while the effect of investment on economic growth cannot be limited by inflation.